Aktualisasi Program Kampus Mengajar Melalui Pelaksanaan Kegiatan Kaya Literasi dan Numerasi di SD Negeri Dungkek III - Efendi, Surya Fajar; Rozie, Fachrur (Satya Widya, 2024)
This research aims to identify activity programs that can be carried out by Kampus Mengajar 7 in an effort to create an environment and habituation to literacy and numeracy activities at SD Negeri Dungkek III. This is motivated by the lack of average ability of Indonesian students in literacy and numeracy in the last 3 years based on PISA data. The main focus of the Kampus Mengajar program is targeting level 1 and 2 schools based on the results of the National Assessment. This research uses descriptive qualitative research methods with data collection techniques, namely interviews, observation and documentation. The results of this research explain the role of students' active contribution in the actualization of the Kampus Mengajar program as teacher partners, socializers of the Ministry of Education and Culture's learning products, technology adaptation, as well as collaborative learning variations in the classroom as well as identifying activity programs that can be implemented to boost students' literacy and numeracy skills.